2019
DOI: 10.31124/advance.8087870.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How the Japanese Term Kawaii is Perceived Outside of Japan- A study in Israel

Abstract: This study illuminates how Israelis define and treat the Japanese term kawaii<br>

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The research protocol was approved by the research ethics committee of the Graduate School of Language and Culture, Osaka University, Japan. A part of the survey that is not reported in this article was published by Lieber-Milo (2017), and a partial report of the Study 1 results was published by Lieber-Milo and Nittono (2019b). Supplemental material for this article is available online at https://osf.io/gcvzk.…”
Section: Methodsmentioning
confidence: 99%
“…The research protocol was approved by the research ethics committee of the Graduate School of Language and Culture, Osaka University, Japan. A part of the survey that is not reported in this article was published by Lieber-Milo (2017), and a partial report of the Study 1 results was published by Lieber-Milo and Nittono (2019b). Supplemental material for this article is available online at https://osf.io/gcvzk.…”
Section: Methodsmentioning
confidence: 99%
“…Since we only conducted our experiment with Japanese participants, generality and cultural differences should be considered. Even though kawaii is an example of a typical element of Japanese culture and such concepts have been spreading worldwide, past studies reported cultural differences about kawaii feelings between China and Japan [40] and Israeli and USA [41,42]. These studies compared the perceived differences of kawaii to Japan, although they also reported that these other cultures held positive views of kawaii/cute concepts.…”
Section: Plos Onementioning
confidence: 98%
“…This study will provide a different perspective on the meaning of the word cute in previous studies [5], especially in Indonesia. The purpose of this study is to examine the dimensions of aesthetic of cuteness to better understand the role of mascot design in the cute style through affective dimensions, language dimensions, and design dimensions.…”
Section: Introductionmentioning
confidence: 94%